Contestation of Global Competencies: The Concepts of 3 Featured Madrasah Ibtidaiyah in Banyumas - Afandi, Rahman; Mustajab (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2018)
The existence of madrasah (Islamic school) management development is essential in Indonesia. Research findings in 2017 show the pattern of educational expansion carried out by madrasahs in each region and education unit. Madrasahs inflate their roles and functions as a means of quality improvement. The expansion can be seen in the progressing number of Madrasah Ibtidaiyah (MI) in Banyumas, reaching a figure of 182. The group MI divided into 179 private institutions and three public ones. The madrasah spread in 27 sub-districts of Banyumas District. Problems faced by MTs in Banyumas in developing their potentials are related to global competencies. The issues have become the homework for madrasah managers who oversee quality excellence. This paper will discuss three featured MIs in Banyumas in relation to the contestation of global competencies in Islamic education management. The three madrasahs are the State Madrasah Ibtidaiyah number 1 Banyumas (MI Negeri 1 Banyumas) as a Distinguished and Islamic School; MI Ma’arif NU Pageraji as a School of Champions; and MI Muhammadiyah Karanglewas Kidul as a School of Quality and Character.